Lighting and controls : transitioning to the future - Walerczyk, Stan (The Fairmont Press, Inc. : CRC Press, 2014)
This book helps you make good lighting decisions and will be a very useful hands-on tool for anyone involved with engineering, maintenance, purchasing, specification, retrofits, remodels, and new construction for interior or exterior lighting applications. It gives very practical ways to maintain and update existing lighting systems and how to plan for the future. Key points include LED lighting, maintenance costs, achieving low power density, disadvantages of LED T8s, and human centric lighting.